Specialized Metabolites from the Allelopathic Plant Retama raetam as Potential Biopesticides - Gabriele Soriano; Claudia Petrillo; Marco Masi; Mabrouka Bouafiane; Aminata Khelil; Angela Tuzi; Rachele Isticato; Mónica Fernández-Aparicio; Alessio Cimmino (Toxins, 2022)
To cope with the rising food demand, modern agriculture practices are based on the indiscriminate use of agrochemicals. Although this strategy leads to a temporary solution, it also severely damages the environment, representing a risk to human health. A sustainable alternative to agrochemicals is the use of plant metabolites and plant-based pesticides, known to have minimal environmental impact compared to synthetic pesticides. Retama raetam is a shrub growing in Algeria’s desert areas, where it is commonly used in traditional medicine because of its antiseptic and antipyretic properties. Furthermore, its allelopathic features can be exploited to effectively control phytopathogens in the agricultural field. In this study, six compounds belonging to isoflavones and flavones subgroups have been isolated from the R. raetam dichloromethane extract and identified using spectroscopic and optical methods as alpinumisoflavone, hydroxyalpinumisoflavone, laburnetin, licoflavone C, retamasin B, and ephedroidin. Their antifungal activity was evaluated against the fungal phytopathogen Stemphylium vesicarium using a growth inhibition bioassay on PDA plates. Interestingly, the flavonoid laburnetin, the most active metabolite, displayed an inhibitory activity comparable to that exerted by the synthetic fungicide pentachloronitrobenzene, in a ten-fold lower concentration. The allelopathic activity of R. raetam metabolites against parasitic weeds was also investigated using two independent parasitic weed bioassays to discover potential activities on either suicidal stimulation or radicle growth inhibition of broomrapes. In this latter bioassay, ephedroidin strongly inhibited the growth of Orobanche cumana radicles and, therefore, can be proposed as a natural herbicide.